Vegetable-based polymer composite: Characterization and application - Malmonge, José Antonio [UNESP]; de Souza, Maria do Carmo Lopes [UNESP]; Malmonge, Luiz Francisco [UNESP]; Sakamoto, Walter Katsumi [UNESP] (My University, 2012)
Composite films of castor oil-based polyurethane (COPU) and polyaniline (PAni) were obtained by two methods. In the first one, the composites were prepared by chemical polymerization of polyaniline in situ onto PU surface, and in the second method, the composite called semi-interpenetrating network (sIPN) were prepared by swelling the polyurethane sheets with aniline followed by immersing the specimen in an aqueous solution of hydrochloric acid (HCl) containing ammonium persulphate as oxidant. A typical coating layer with electrical conductivity around 10° S/cm, with excellent adhesion and transparency between 50 to 60% in the range of 475 to 605 nm were obtained. The maximum thickness was reached in one hour of immersion for polymerization at 0°C. The layer thickness showed to be dependent on time immersion and the aniline polymerization temperature. The bulk conductivity and surface resistivity were found around 10-4 S/cm and 105 ω/?, respectively for the composite obtained by swollen method. These composites are thermally stable up to 90°C and showed a globular morphology. DSC spectra showed a shift around 15°C, to high temperature direction, on the glass transition temperature for the sIPN composite, and the UV-vis-NIR spectra showed a typical spectrum of doped polyaniline. Besides the use of a polymer from a renewable source, the results on the control of electrical conductivity indicate that the composite films obtained can be used for purposes such as antistatic and electromagnetic shielding. © 2012 Nova Science Publishers, Inc. All rights reserved.